ELEKTRONIK COMMERCE (JUAL BELI ONLINE) DI TINJAU DARI SISI MASLAHAH - jafar, wahyu abdul (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2015)
This study describes the the law of electronic commerce transactions (buying and selling online) viewed from the side maslahah.In this study described how ber-istinbath using maslahah,starting with electronic commerce persolan description in detail, followed by synchronization and verification of the condition argues maslahah with the benefits of manfat contained in electronic commerce and final legal justification process electronic commerce transactions (buying and selling online ). From this study obtained two conclusions: First, the benefits of electronic commerce transactions already meet the requirements for use as the basis ofber-proof using maslahah. Secondly, the law of electronic commerce transactions (buying and selling online) can be changed to follow the situation and conditions of the transaction, which could turn out to be permissible and could also turn out to be illegitimate. Permissible if electronic commerce transactions could lead to the realization of intiqolil Milki (in accordance with the transfer of ownership of goods purchased) from the seller into the hands of the buyer. While electronic commerce laws turn out to be illegitimate if it does not materialize intiqolil Milki (transfer of ownership in accordance with the purchased goods).